Literasi dan Inklusi Keuangan Syariah Perempuan Muslim di Perumahan Elite the Argopuro Jember - Mahfiyah, Mahfiyah (Universitas Islam Raden Rahmat, 2025)
Financial literacy and inclusion are one of the government's programs. It has remained an important issue in recent years. Although there are many studies on Islamic financial literacy and inclusion, it is still rare to target Muslim women in Elite Residential. The purpose of this study is to find out how Islamic financial literacy and inclusion in Muslim Women in The Argopuro Jember Elite Residential. The method used in this study is qualitative. The primary data in this study is Muslim women in Argopuro tea Housing while the secondary data comes from journals or books. The results of this study show that Islamic financial literacy and inclusion in Muslim women in The Argopuro Residential in Jember is still low and needs to be improved. It is inversely proportional to conventional financial literacy and inclusion which is quite good. This research can be a consideration for policy makers in determining strategies to increase Islamic financial literacy and inclusion in Indonesia, especially for women from various social classes.